Hal-hal Yang Memotivasi Mahasiswa Dalam Menelusuri Informasi di Perpustakaan Fakultas Kedokteran Universitas Andalas - Sari, Sumita; Nst., Bakhtaruddin (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this research are describing: 1) the things that motivate university students in investigating information at Medical Faculty Library of Andalas University, 2) the factors that dominantly motivate university students in investigating information at Medical Faculty Library of Andalas University. The data were collected through observation and spreading questionnaire to the university students.Â  Data analysis was done descriptively. Based on analyzed data, we can conclude that: First, the things that motivate university students in investigating information are: 1) sometimes librarian help university students to find materials that they need, 2) the university students have had objective that they want to reach, 3) the university students will be motivated if the information that is given by the librarian is attractive, 4) the librarians give admission to the university students, 5) the university students will be motivated if they are participated in a group, 6) doing the things that really motivate the university students, 7) the challenge will give motivation to the university students, 8) the university students need motivation support, 9) togetherness will motivate the university students. Second, the factors that dominantly motivate the university students in investigating information at Medical Faculty Library of Andalas University is internal factor that is come from the university students themselves. Keywords: motivation; information Â